Regulation of the segmentation gene fushi tarazu has been functionally conserved in Drosophila. - Maier, D (1990)
An evolutionary approach was applied to identify elements involved in the regulation of the segmentation gene fushi tarazu (ftz) by comparing the Drosophila melanogaster ftz gene with its Drosophila hydei homologue. The overall organization of the ftz gene is very similar in both species. Surprisingly, ftz proved to be inverted in the ANT-C of D. hydei with respect to D. melanogaster. Strong homologies extend over the entire 6 kb of the ftz upstream region with the best match in the 'upstream element'. We identified several highly conserved boxes embedded in unrelated sequences that correspond extremely well to two germ layer specific enhancers in the upstream element. Transformation experiments revealed that D. hydei ftz gene products can restore D. melanogaster ftz function and, furthermore, that trans-acting factors from D. melanogaster recognize and control D. hydei ftz regulatory elements. These findings indicate a conservation of the entire regulatory network among segmentation genes for several millions of years during the evolution of Drosophila.